Reliability of bounce drop jump parameters within elite male rugby players - Costley, L.; Wallace, E.; Johnston, M.; Kennedy, R. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aims of the study were to investigate the number of familiarization sessions required to establish reliability of the bounce drop jump (BDJ) and subsequent reliability once familiarization is achieved. METHODS: Seventeen trained male athletes completed 4 BDJs in 4 separate testing sessions. Force-time data from a 20 cm BDJ was obtained using two force plates (ensuring ground contact <250 ms). Subjects were instructed to "jump for maximal height and minimal contact time" while the best and average of four jumps were compared. A series of performance variables were assessed in both eccentric and concentric phases including jump height, contact time, flight time, Reactive Strength Index (RSI), peak power, rate of force development (RFD) and actual dropping height (ADH). Reliability was assessed using the intraclass correlation coefficient (ICC) and coefficient of variation (CV) while familiarization was assessed using a repeated-measures analysis of variance (ANOVA). RESULTS: The majority of DJ parameters exhibited excellent reliability with no systematic bias evident, while the average of 4 trials provided greater reliability. With the exception of vertical stiffness (CV: 12.0%) and RFD (CV: 16.2%), all variables demonstrated low within subject variation (CV range: 3.1-8.9%). Relative reliability was very poor for ADH, with heights ranging from 14.87-29.85 cm. CONCLUSIONS: High levels of reliability can be obtained from the BDJ with the exception of vertical stiffness and RFD, however, extreme caution must be taken when comparing DJ results between individuals and squads due to large discrepancies between actual drop height and platform height.